Advancement in nanotechnology-based approaches for the treatment and diagnosis of hypercholesterolemia. (31st October 2018) - Gupta, Nidhi; Sharma, Nikita; Mathur, Sandeep K.; Chandra, Ramesh; Nimesh, Surendra
Abstract: Cardiovascular diseases have been the major cause of mortality and morbidity all over the world accounting for more than 80% of the deaths from heart attacks and strokes. Hypercholesterolemia, an autosomal disorder of lipoprotein metabolism is one of the foremost causes of CVDs. An increased level of low-density lipoprotein cholesterol (LDL-C) in the plasma results in the rise of incidence rates in disease patients. Several conventional and combinational therapies have been proposed for lowering the LDL-C levels in the blood. These therapeutic agents are designed to target some crucial molecules that participates in the lipid metabolism such as apolipoprotein B, HMGCoA reductase, proprotein convertase subtilisin/kexin 9, etc. Although these therapies are effective but are associated with certain side effects. This article presents an overview on different conventional and nanotechnology-based approaches for the treatment and diagnosis of hypercholesterolemia. Numerous nanomaterial-based therapies including polymeric nanoparticles, cationic lipids, liposomes, dendrimers and inorganic nanoparticles have been discussed in lowering the cholesterol level along with recent advancement in diagnosis and imaging.